Sex and Gender Differences in Bacterial Infections - Dias, Sara P; Brouwer, Matthijs C; van de Beek, Diederik (Infection and immunity, 2022)
There is a growing awareness of the importance of sex and gender in medicine and research. Women typically have stronger immune responses to self and foreign antigens than men, resulting in sex-based differences in autoimmunity and infectious diseases. In both animals and humans, males are generally more susceptible than females to bacterial infections. At the same time, gender differences in health-seeking behavior, quality of health care, and adherence to treatment recommendations have been reported. This review explores our current understanding of differences between males and females in bacterial diseases. We describe how genetic, immunological, hormonal, and anatomical factors interact to influence sex-based differences in pathophysiology, epidemiology, clinical presentation, disease severity, and prognosis, and how gender roles affect the behavior of patients and providers in the health care system.